Influence of Geometric Parameters on Fatigue Life of Two-Planar Tubular DKT Joints Based on Fracture Mechanics Under a Combination Loading - Muhammad Akbar Hardian; Rudi Walujo Prastianto; Ilham Kurniawan (Department of Ocean Engineering, 2025)
According to SKK Migas, Indonesia has operated 613 units of offshore platforms which is 54.65% of the platforms are more than 20 years old, and 24.63% are between 16-20 years old. With the extension of its operation time, the structural integrity of the old platform will decrease. One of the potential consequences is structural failure due to cyclical loading caused cracks. . This research aims to determine the influence of geometric parameters in DKT twoplanar tubular joints on fatigue life based on fracture mechanics. By varying geometric parameters, we can see the influence of geometric parameters on fatigue life under combined loads of axial, in-plane bending, and out-of-plane bending moments. The tubular joints are modeled locally and analyzed using Finite Element Analysis (FEA), and the crack is modeled as a semi-elliptical form. Fatigue life analysis is performed by varying geometric parameters under the combined loads. After carrying out a sensitivity analysis on all geometric parameters, it was concluded that the gamma parameter had the most influence on the combined load with a sensitivity of 89%.